2004
DOI: 10.1016/j.jtcvs.2004.02.042
|View full text |Cite
|
Sign up to set email alerts
|

First human transplantation of a bioengineered airway tissue

Abstract: the sternum veins bears some similarity to the opening of the cranial vault veins, and disconnecting the endotracheal tube just before sternotomy decreases airway pressure. Furthermore, 5 (25%) of our patients had a preexisting right-to-left shunt, again increasing the likelihood of clinically significant VAE. The fact that embolus incidence was higher with the saw compared with the scissors is not straightforward. It would seem that the saw would result in less compression of the bone marrow, thus being less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 164 publications
(110 citation statements)
references
References 3 publications
0
103
0
7
Order By: Relevance
“…Recent preliminary clinical studies have shown ECM scaffolds provide a viable option for patients who previously had none [148]. This approach utilizes decellularized human tracheas prepared via a detergent enzymatic method with sodium deoxycholate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent preliminary clinical studies have shown ECM scaffolds provide a viable option for patients who previously had none [148]. This approach utilizes decellularized human tracheas prepared via a detergent enzymatic method with sodium deoxycholate.…”
Section: Discussionmentioning
confidence: 99%
“…Decellularized aortic grafts [147], jejunum [148,149,150], bladder [151], and trachea [151,152,153,146] …”
Section: Decellularized Tissuementioning
confidence: 99%
See 3 more Smart Citations